Characteristics and kinetics study of spherical cellulose nanocrystal extracted from cotton cloth waste by acid hydrolysis - Thi Kim Quyen Doan; Kung Yuh Chiang (Sustainable Environment Research, 2022)
Abstract This work investigated the extraction of spherical cellulose nanocrystal (spherical CNC) from cotton cloth waste (CCW) using sulfuric acid without ultrasound treatment during the hydrolysis process, producing a yield of 31%. The cellulose was first extracted through alkali, decoloring, and hydrochloric acid treatment. Then the cellulose was hydrolyzed using 55 wt% sulfuric acid with various acid to cellulose ratios, including 30:1, 40:1, and 50:1 mL g− 1. The resulting CNC was characterized by morphological structure, functional groups, crystalline structure, elemental compositions, thermal degradation kinetic, and zeta potential. The analytical results revealed that the acid to cellulose ratios significantly influenced the properties of CNC obtained. The morphological structure showed that when the acid to cellulose ratio was 30:1 and 40:1 mL g− 1, the rod-like CNC was observed with a length of 53 ± 19 nm and 49 ± 13 nm; a width of 6.6 ± 1.3 nm and 4.3 ± 2.0 nm, respectively. However, when the acid to cellulose ratio was further increased to 50:1 mL g− 1, the nanocellulose morphology turned to be spherical, with an average diameter of 14.4 nm. Furthermore, spherical CNC exhibited better characteristics consisting of crystallinity index (94.6%) and stable dispersibility with zeta potential value − 46.8 mV than rod-like CNC. However, the thermal stability of spherical CNC was slightly lower than that of rod-like CNC. The kinetic results indicated that the activation energy of spherical CNC ranged from 134 to 423 kJ mol− 1, which is lower than that (145 to 651 kJ mol− 1) of rod-like CNC ranging from. This study showed that the CCW is a potential low-cost cellulose source to manufacture spherical CNC and a good example for developing a circular economy.